From Campus to the Public Arena: Institutional Educational as the Vanguard of Anti-Corruption Efforts - Ananda Chrisna D. Panjaitan; Torang Fadly Panjaitan; Clarissa Aurelia Leowinata (Universitas Negeri Semarang, 2025)
Corruption remains a persistent and systemic problem in Indonesia, underscoring the urgency of preventive strategies that extend beyond law enforcement to the education sector. Law faculties play a strategic role in cultivating integrity and ethical awareness among students as future legal professionals. Nevertheless, the integration of anti-corruption values within legal education has yet to be implemented in a comprehensive and systematic manner. This article examines the integration of anti-corruption education in law higher education institutions and identifies the principal obstacles to its effective implementation. This study adopts normative juridical research supported by conceptual and sociological perspectives, drawing on secondary legal materials to analyse the regulatory framework, theoretical foundations, and practical implementation of anti-corruption education within the academic environment. The findings demonstrate that the main challenges in anti-corruption education include weak curricular integration, the absence of consistent ethical role models among educators, a permissive academic culture, and limited institutional cooperation with law enforcement and anti-corruption agencies. To address these issues, the study proposes a comprehensive strategy encompassing the strengthening of an integrity-based curriculum, the institutionalisation of transparent and accountable academic governance, the development of ethical leadership among lecturers, and structured collaboration with anti-corruption institutions. The article concludes that law faculties can function as the vanguard of corruption prevention by systematically embedding integrity values within legal education, thereby contributing to the formation of a generation capable of promoting a clean, accountable, and just public order in Indonesia.